2022
DOI: 10.1038/s41598-022-15080-2
|View full text |Cite
|
Sign up to set email alerts
|

Zinc nutritional status, mood states and quality of life in diarrhea-predominant irritable bowel syndrome: a case–control study

Abstract: Zinc is an important trace element for structure, and regulation in the central nervous system, as well as the gut homeostasis. There are several mental disorders associated with zinc deficiency. The relationship between zinc nutritional status with mood states and quality of life (QoL) in diarrhea-predominant irritable bowel syndrome (IBS-D) has not been studied yet. This case–control study aimed to investigate the association between zinc nutritional status with mood states and QoL in IBS-D patients. Sixty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In the study of Van Lanen et al, it was determined that a low-FODMAP diet reduced IBS symptoms and improved quality of life 15 . A relationship was found between dietary zinc intake and body image and psychological health in patients in another study 16 . In the study of Melchior et al, a significant relationship was found between low quality of life and severe food avoidance and restriction 17 .…”
Section: Introductionmentioning
confidence: 85%
“…In the study of Van Lanen et al, it was determined that a low-FODMAP diet reduced IBS symptoms and improved quality of life 15 . A relationship was found between dietary zinc intake and body image and psychological health in patients in another study 16 . In the study of Melchior et al, a significant relationship was found between low quality of life and severe food avoidance and restriction 17 .…”
Section: Introductionmentioning
confidence: 85%
“…Energy intake was analyzed from 24 studies 11,15,16,18,44,46,[48][49][50]54,62,63,69,72,86,87,[89][90][91][92]94,98,103,104 There were no differences across study quality subgroups.…”
Section: Energymentioning
confidence: 99%
“…Fiber intake was analyzed from 24 studies 11,15,16,43,44,[48][49][50]54,56,63,66,68,69,86,87,[89][90][91]94,98,[102][103][104][105] (N = 3388 participants with IBS, N = 7179 controls) to demonstrate lower intake in participants with IBS compared to controls with high heterogeneity (MD: −1.8 g; 95% CI: −3.0, −0.6; I 2 = 85%, Figure 3).…”
Section: Total Fibermentioning
confidence: 99%
See 2 more Smart Citations